Kajian Pemilihan Moda Transportasi Rute Bandara Kuala Namu – Medan - Sipangkar, Debi Irawan; Sitindaon, Charles (Jurnal Rekayasa Konstruksi Mekanika Sipil, 2018)
Transportation is defined as the process of moving passengers or goods from one place to another. In transportation planning, mode choice analysis is one of the important things that needs to be conducted in order to obtain traveler’s reasoning and factors that affect their choices. In this study, we conducted mode choice analysis for Kuala Namu airport to Medan trip. Several factors that areinfluential to mode choice are safety, convenience, cost, and travel time. We use Analytical Hierarchy Process (AHP) to analyze the weight of importance of these factors according to the travelers. Questionnaires were distributed followed by interview with respondents that actually make the trip between the two places. The result shows that safety (51.93%) is the main important factor, followedby convenience (36.11%), cost (24.04%), cost (9.01%), and travel time (2.95%). In terms of preferred mode according to travelers, train and private car are the best alternative with the value of 45.20% and 41.75% respectively. The least favorable alternatives are bus (7.43%) and taxi (5.62%).